Raising Climate Change Awareness Through Community Environmental Education: A Case Study Of “One World, One Goal” Project - Baras, Andrés; Maddi, Maddi (Civiliza Publishing, Indonesia., 2024)
Given the increasing importance of environmental awareness, it is now widely acknowledged that environmental education should be introduced and ingrained from a young age, both in formal educational settings and within the family environment (non-formal education). The present case study examines the implementation and outcomes of a pioneering project,